Seasonal water use strategy of canopy tree species and possible implication for their coexistence in a subtropical secondary forest. Issue 7 (15th July 2019) - Ouyang, Lei; He, Wen; Huang, Kechao; Zhou, Cuiming; Gu, Daxing; Huang, Yuqing; Zhao, Ping
Abstract: We investigated the seasonal water use patterns of five canopy tree species, Schima superba, Liquidambar formosana Hance, Quercus griffithii Hook, Quercus acutissima Carruth, and Pinus massoniana, in a subtropical secondary forest in Guangxi province, which were pervasively planted in South China. The hypothesis is that the trees can make different temporal use of environmental resources that change seasonally and consequently contribute to their coexistence. Sap flow technique was used to measure the daily and seasonal transpiration during the period from June 2016 to May 2017. The sap flow—derived daily transpiration ( E L ), leaf water potential (Δ Ψ ), hydraulic conductance ( K ), as well as the responses of E L to driving factor—water vapour pressure deficit ( VPD ) was determined in dry and wet seasons. Measured data of stem sap flow showed that L. formosana, Q. griffithii, and P. massoniana transpired more water than S. superba and Q. acutissima during the whole monitoring period, whereas daily E L of P. massoniana rapidly decreased under dry season. We attributed the different water use patterns to the significant difference in Δ Ψ, K, and wood density among the five species. Moreover, linear relationships between the daily transpiration and VPD might suggest diverse water use strategies. For the species of S. superba, Q. acutissima, and P. massoniana, less water consumption and relatively flat change of transpiration with VPD were observed, suggesting a relatively tighter stomatal control. The slope values for L. formosana and Q. griffithii, which were much higher even under dry season, might own a weak stomatal control. These different functional and hydraulic traits, together with the associated water use strategies, might facilitate the coexistence of these five canopy tree species, which would assist in predicting the impact of future environmental changes on plant biodiversity and ecosystem services in the investigated region.